Independent Woman in The Korean Drama The World of The Married: Feminism Theory - Nisrina Nur Lathifah; Nurhidayat (Universitas Cokroaminoto Palopo, 2024)
This research raises the topic of independent women who are considered to have a respected attitude or are not easily looked down upon by society. In the Korean drama entitled The World Of The Married, the main character Ji Sun Woo dis-plays an independent female character who is very strong, independent, success-ful in her career, and lives happily in the drama. This research explores the inde-pendent female character in Ji Sun Woo's character but also finds out the direc-tor's reasons for remaking the drama The World Of The Married from the Doctor Foster series, as well as knowing the impact of an affair. the method in this study uses descriptive qualitative research methods, as well as data collection through secondary data. The results of this study indicate that women are not easily un-derestimated and must be respected, as well as when a woman is cheated on or divorced she can become an independent woman without having to depend on men.